High-resolution molecular typing of trypanosoma cruzi in 2 large outbreaks of acute chagas disease in Colombia (2016)
Oral transmission of Trypanosoma cruzi has gained relevance because of its association with high morbidity and lethality rates. This transmission route is responsible for maintaining the infection of the parasite in sylvatic cycles, and human cases have been associated mainly with the consumption of food contaminated with triatomine feces or didelphid secretions. Several ecological changes allow the intrusion of sylvatic reservoirs and triatomines to the domestic environments with subsequent food contamination. Here, high-resolution molecular tools were used to detect and genotype T. cruzi across humans, reservoirs, and insect vectors in 2 acute outbreaks of presumptive oral transmission in eastern Colombia.